2021
DOI: 10.1101/2021.08.16.456588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The clinical utility of two high-throughput 16S rRNA gene sequencing workflows for taxonomic assignment of unidentifiable bacterial pathogens in MALDI-TOF MS

Abstract: Bacterial pathogens that cannot be identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) are occasionally encountered in clinical laboratories. The 16S rRNA gene is often used for sequence-based analysis to identify these bacterial species. Nevertheless, traditional Sanger sequencing is laborious, time-consuming and low-throughput. Here, we compared two commercially available 16S rRNA gene sequencing tests, which are based on Illumina and Nanopore sequenci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Eikenella mostly colonizes on the mucosal surface, but it can also invade the surrounding tissues and cause infection. Previous studies revealed that it can cause oral infection, respiratory tract infection, liver abscess, neck abscess, meningitis, conjunctivitis, osteomyelitis, etc., but the incidence is low worldwide ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eikenella mostly colonizes on the mucosal surface, but it can also invade the surrounding tissues and cause infection. Previous studies revealed that it can cause oral infection, respiratory tract infection, liver abscess, neck abscess, meningitis, conjunctivitis, osteomyelitis, etc., but the incidence is low worldwide ( 19 ).…”
Section: Discussionmentioning
confidence: 99%